2013
DOI: 10.1038/mp.2013.147
|View full text |Cite
|
Sign up to set email alerts
|

Central 5-HT4 receptor binding as biomarker of serotonergic tonus in humans: a [11C]SB207145 PET study

Abstract: Identification of a biomarker that can inform on extracellular serotonin (5-HT) levels in the brains of living humans would enable greater understanding of the way brain circuits are modulated by serotonergic neurotransmission. Substantial evidence from studies in animals and humans indicates an inverse relationship between central 5-HT tonus and 5-HT type 4 receptor (5-HT4R) density, suggesting that 5-HT4R receptor density may be a biomarker marker for 5-HT tonus. Here, we investigated whether a 3-week admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 36 publications
(49 reference statements)
8
79
0
Order By: Relevance
“…2) and established normative data for the 5-HTT , the 5-HT 2A (Adams et al, 2004) and the 5-HT 4 (Madsen et al, 2011b) receptors. A novel agonist radioligand for 5-HT 2A receptor PET studies, [11C]Cimbi-36, has also been developed and validated in humans (Ettrup et al, 2014) and 5-HT 4 receptor binding has been shown to be inversely related to 5-HT brain levels (Fisher et al, 2012;Haahr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2) and established normative data for the 5-HTT , the 5-HT 2A (Adams et al, 2004) and the 5-HT 4 (Madsen et al, 2011b) receptors. A novel agonist radioligand for 5-HT 2A receptor PET studies, [11C]Cimbi-36, has also been developed and validated in humans (Ettrup et al, 2014) and 5-HT 4 receptor binding has been shown to be inversely related to 5-HT brain levels (Fisher et al, 2012;Haahr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent initiatives include work with the 5-HT 4 receptor antagonist [ 11 C]SB207145 19 and the 5-HT 2A receptor agonist [ 11 C]Cimbi-36. Initial evaluation of [ 11 C]Cimbi-36 demonstrated serotonin sensitivity with changes that are detectable with PET when the serotonin release is sufficiently high 20 .…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 99%
“…All participants were generally healthy (see Supplementary Materials and Methods for more details) as described previously (Haahr et al, 2014). Of the 35 participants who were recruited for the study, four did not complete the entire protocol (two because of PET scanner failure, one elected to dropout, and one did not complete the fMRI paradigm).…”
Section: Participantsmentioning
confidence: 99%
“…Thus, our sample consisted of 31 individuals. fMRI data included here have not been previously described, whereas PET data included here have been reported previously (Fisher et al, 2012;Haahr et al, 2014;Haahr et al, 2013).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation